Disordered eating in high performance sport position statement. The Australian Institute of Sport (AIS) and National Eating Disorders Collaboration (NEDC) position statement on disordered eating in high performance sport - Wells, K.; Jeacocke, N.; Appaneal, R.; Smith, H.; Vlahovich, N.; Burke, L.; Hughes, D. (Australian Institute of Sport (AIS) and National Eating Disorders Collaboration (NEDC), 2020)
The identification, evaluation and management of disordered eating is complex. Disordered eating exists on a spectrum from optimised nutrition through to clinical eating disorders. Individual athletes can move back and forth along the spectrum of eating behaviour at any point in time over their career and within different stages of a training cycle. Athletes are more likely to present with disordered eating than a clinical eating disorder. Overall, there is a higher prevalence of disordered eating and eating disorders in athletes compared to non-athletes. Additionally, athletes participating in aesthetic, gravitational and weight-class sports are at higher risk of disordered eating and eating disorders than those in sports without these characteristics. The evaluation and management of disordered eating requires a cohesive team of professional practitioners consisting of, at minimum, a doctor, a sports dietitian and a psychologist, termed within this statement as the core multidisciplinary team. The Australian Institute of Sport and the National Eating Disorders Collaboration have collaborated to provide this position statement, containing guidelines for athletes, coaches, support staff, clinicians and sporting organisations. The guidelines support the prevention and early identification of disordered eating, and promote timely intervention to optimise nutrition for performance in a safe, supported, purposeful and individualised manner. This position statement is a call to action to all involved in sport to be aware of poor self-image and poor body image among athletes. The practical recommendations should guide the clinical management of disordered eating in high performance sport.